The third gate : a novel - Child, Lincoln (Child, Lincoln. Jeremy Logan series., 2012)
Professor Jeremy Logan is brought onto famed explorer Porter Stone's archaeological team to investigate a series of harrowing and inexplicable occurrences that are causing people on the expedition to fear a centuries-old curse behind Pharoah Narmer's elusive "double" crown of the two Egypts.